The efficacy of a multifactorial memory training in older adults living in residential care settings - Vranić, Andrea (Array, 2013)
Background: Several studies have shown an increase in memory performance after teaching mnemonic techniques to older participants. However, transfer effects to non-trained tasks are generally either very small, or not found. Methods: The present study investigates the efficacy of a multifactorial memory training program for older adults living in a residential care center. The program combines teaching of memory strategies with activities based on metacognitive (metamemory) and motivational aspects. Specific training-related gains in the Immediate list recall task (criterion task), as well as transfer effects on measures of short-term memory, long-term memory, working memory, motivational (need for cognition), and metacognitive aspects (subjective measure of one's memory) were examined. Maintenance of training benefits was assessed after seven months. Fifty-one older adults living in a residential care center, with no cognitive impairments, participated in the study. Participants were randomly assigned to two programs: the experimental group attended the training program, while the active control group was involved in a program in which different psychological issues were discussed. Results: A benefit in the criterion task and substantial general transfer effects were found for the trained group, but not for the active control, and they were maintained at the seven months follow-up. Conclusion: Our results suggest that training procedures, which combine teaching of strategies with metacognitive-motivational aspects, can improve cognitive functioning and attitude toward cognitive activities in older adults.